Concentrations of lead (pb) in road dust in bandar seri begawan, brunei darussalam - Shahrizal Emran,; K. Rodney Fernando,; and Miroslav Radojevic Radojevic (ASEAN Journal on Science and Technology for Development, 2001)
A first-ever survey oflead (Pb) in road dust in Bandar Seri Begawan (B.S.B.), the capital of Brunei Darussalam, was carried out in 1996, three years after the introduction of unleaded petrol. The concentration of Pb at 114 sites varied between 12 and 544 µg/g (mean: 125 µg/g; standard deviation: 103 µg/g). There was a significant correlation (r=0.546) between lead in road dust and traffic volume at 17 sites for which traffic counts were available. An assessment of the potential hazard posed to children was made. It is concluded that concentration levels of Pb in road dust in B.S.B. are considerably lower than levels found in London and Hong Kong, and they do not pose a major public health hazard.